2020
DOI: 10.1111/jcmm.15934
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic silver/silver chloride nanoparticles inhibit human glioblastoma stem cells growth in vitro and Ehrlich ascites carcinoma cell growth in vivo

Abstract: The importance of biogenic silver/silver chloride nanoparticles has become increasing day by day. In the present study, silver/silver chloride nanoparticles (Ag/AgCl‐NPs) were synthesized from Kaempferia rotunda tuberous rhizome extract to evaluate the antiproliferative activity against human glioblastoma stem cells (GSCs) in vitro and Ehrlich ascites carcinoma (EAC) cells in vivo in mice. Synthesis of nanoparticles was confirmed by colour change and UV‐visible spectrum and characterized by TEM, XRD, TGA, AFM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…XRD proved the crystalline nature of the synthesised nanoparticles and showed the peaks for Ag and AgCl. Many scientists reported similar observations [22,24,33] [34]. The peak at 2920.32 cm −1 indicated CH stretching of alkanes [30].…”
Section: Discussionmentioning
confidence: 64%
“…XRD proved the crystalline nature of the synthesised nanoparticles and showed the peaks for Ag and AgCl. Many scientists reported similar observations [22,24,33] [34]. The peak at 2920.32 cm −1 indicated CH stretching of alkanes [30].…”
Section: Discussionmentioning
confidence: 64%
“…So far, it is difficult to draw definite conclusions from these studies given that different AgNPs formulations are used on different cancer models with different dosing and administration schemes. In particular, it should be recognized that in most of the studies involving testing of AgNPs anticancer activity in vivo, biologically synthesized, “biogenic” AgNPs are used [ 9 , 10 , 11 , 12 , 13 , 35 ]. Biological synthesis involves the use of extracts from different organisms, such as bacteria, fungi, algae, or plants, and obtained nanoparticles are coated with proteins and compounds derived from these extracts.…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency with other reports is probably due to differences in AgNPs formulation or administration route. In in vivo studies published to date, AgNPs were administered peritumorally [ 15 , 17 ], subcutaneously [ 16 ], intraperitoneally [ 10 , 11 , 13 ], intravesically [ 9 ], or intravenously [ 14 ]. To the best of our knowledge, the present study is the first report on anticancer AgNPs activity after intragastrical administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an anticancer and antibacterial effect was achieved using Zizyphus mauritiana fruit or Kaempferia rotunda (a medical herb) tuberous rhizome extract-mediated silver/silver chloride (Ag/AgCl) NPs. Usage of this nanotool against human GBM stem cells (GSCs) in vitro or Ehrlich ascites carcinoma cells in vivo (mice model) showed the induction of cell cycle arrest at the G2/M phase and reduction of the growth rate of GBM cells [ 90 ]. Other studies have further confirmed that AgNPs interfere with certain molecular pathways connected to inflammation or cellular repair processes, such as the mitogen-activated protein kinase (MAPK) cascade, in human glial cells [ 91 ].…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%